Polish cities in transition – balance of changes in spatial development -opportunities and threats arising from integration with European Union - Tadeusz Markowski (European Regional Science Association (ERSA), 2004)
The paper deals with urban development processes in Poland in the historical context. These processes are confronted with Western European urban development pattern. The author focuses its considerations on specific developments and distortion aspects like historical huge scale war devastations and large scale developments from the period of centrally planned economy. The influence of these events on dynamic and cycles of present-day urban processes and urban policy challenges is analyzed. In conclusions author suggests that Poland has own specific business and urban cycles, which makes Poland different than its neighboring countries. Past historical development has left is a strong footprint which should be taken very seriously in contemporary national urban policy.
Keywords: 330